STUDI PERFORMANCE BATERE AIR LAUT YANG MENGGUNAKAN ELEKTRODA KARBON AKTIF UNTUK MENGHASILKAN ENERGI LISTRIK - ., Warih Budisantoso (Faculty of Engineering, Universitas Tanjungpura, 2014)
Electrolytic Zinc (Zn) and CarbonElectrodes (C) when inserted in a solution with acertain level of concentration of sea water will giverise to electrical energy due to changes in chemicalreaction is the electrical potential differencebetween two electrodes, so as to generate electricalenergy then take the measurement to get themaximum resultsKeyword : seawater solution, carbon, zinc